Digital coherent optical systems architecture and algorithms - De Arruda Mello, Darli Augusto; Barbosa, Fabio Aparecido (Springer, 2021)
This textbook details the architecture of a digital coherent optical system and describes its main digital signal processing (DSP) algorithms. The authors first show how the combination of advanced modulation techniques, DSP and coherent detection has led to significant gains in capacity and ease of operation. The authors follow the path of the information from its generation in the transmitter, to propagation through the fiber and processing by the DSP algorithms in the receiver. The work summarizes academic results and presents them in a didactic way to students and practitioners working on the area of optical communications. A full suite of classroom materials is included for easy integration into a curriculum, containing theoretic and simulation problems, and off-the-shelf Matlab/Octave functions. Describes in detail the architecture of a digital coherent optical system and presents the main digital signal processing algorithms deployed in these systems; Includes brief introductions and context for each topic before diving into the details, so students get both the big picture and the particulars of the various facets of the systems; Includes a suite of supplementary material with exercises and Matlab/Octave functions for easy use in a classroom environment.